At overskride mennesket – Interview med Francis Fukuyarma om transhumanisme - Bek-Thomsen, Jakob; Lassen, Frank; Thorup, Mikkel (Slagmark - Tidsskrift for idéhistorie, 2018)
The interview with the American political scientist Francis Fukuyama deals with what he once called ‘the most dangerous idea in the world’, namely transhumanism. Transhumanism is the intentional redesign of the human body to make it faster, smarter and healthier, ultimately to free it from the constraints of a corporeal existence and to live forever. Fukuyama is asked to reflect on the philosophical, moral and political dilemmas of the new technologies for designing human life and on the failed opportunities of not engaging oneself as individual and community in these new opportunities.